Permanent Stained Agar Preparation of Mycoplasma and of L Forms of Bacteria - Dienes, Louis (1967)
A procedure is described that permits the preparation of permanent stained mounts of Mycoplasma and of bacterial L forms grown on the surface of and within agar media. These preparations are especially useful for making representative photographs. The cultures are fixed with Formalin vapor. Thin slices of agar are stained at elevated temperature between 50 and 60 C and at a low pH, are dried rapidly, and are mounted in Canada balsam. The results with this staining procedure are illustrated by photographs of various strains of Mycoplasma and of bacterial L forms.